INFLUENCE OF PROMOTION STRATEGIES ON GROWTH OF SMALL AND MEDIUM WATER BOTTLING ENTERPRISES IN KENYA - Ndegwa, Kimani; Ngugi, Dr. Patrick Karanja; Muturi, Dr. Willy Mwangi (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The water sector has the potential to substantially improve the lives of Kenyans by ensuring access to clean water and acceptable sanitation services. Kenya’s bottled water market has 720 registered players of which 59 percent are based in Nairobi Region. The market though is dominated by half a dozen large firms who account for 60 percent of the total sales compared to 40 percent for small and medium enterprises (SMEs). The study found strong relationship between promotion strategies and growth of SME water bottling firms in Kenya. However preference and usage for any of the strategies was strongly attributed to the cost, convenienceand to a lesser extent technology. SMES should thus leverage on low cost but effective marketing strategies to allow them to compete with large firms. This could be discerned from the bold